2016
DOI: 10.4172/2167-0889.1000195
|View full text |Cite
|
Sign up to set email alerts
|

Scoring Systems and Risk Stratification in Cirrhotic Patients with Acute Variceal Bleeding "Scoring in Variceal Bleeding"

Abstract: Objectives: To find the most accurate, suitable and applicable scoring system used for prediction of outcome in cirrhotic patients with bleeding varices. Methods:This prospective study included 120 cirrhotic patients with acute variceal bleeding, admitted at Department of Tropical Medicine and Gastroenterology in Sohag University Hospital over a one-year period (1/2015 to 1/2016). Clinical, laboratory and endoscopic parameters were studied, Child-Pugh (CTP) classification score, Model for end-stage liver disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Scoring that can predict poor outcomes in variceal bleeding, which is a disease-specific condition associated with upper gastrointestinal bleeding and cirrhosis, is focused on the prognosis of liver disease, as predicted by the MELD or Child–Pugh scores [ 2 ]. Existing upper gastrointestinal bleeding (UGIB) scores require various laboratory data and physical examination findings, such as history, ascites through ultrasonography, cardiac function evaluation, endoscopic findings, and dynamic blood pressure changes, heart rate, and level of consciousness [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scoring that can predict poor outcomes in variceal bleeding, which is a disease-specific condition associated with upper gastrointestinal bleeding and cirrhosis, is focused on the prognosis of liver disease, as predicted by the MELD or Child–Pugh scores [ 2 ]. Existing upper gastrointestinal bleeding (UGIB) scores require various laboratory data and physical examination findings, such as history, ascites through ultrasonography, cardiac function evaluation, endoscopic findings, and dynamic blood pressure changes, heart rate, and level of consciousness [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute variceal bleeding (AVB) is a severe complication of portal hypertension that is caused by rupture of the esophageal or gastric varix [ 1 ]. The prognosis of patients with AVB is associated with liver-disease severity [ 2 ]. The Child–Pugh and model end-stage liver disease (MELD) scores have been traditionally used [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although AIMS65 score was not significantly different from MELD, SOFA, and APACHEII scores, it was the best among them in prediction of mortality. 16…”
Section: In a Retrospective Study Done By Sung Min Park Et Al That Inmentioning
confidence: 99%
“…This study included 120 cirrhotic patients with acute variceal bleeding, admitted at Department of Tropical Medicine and Gastroenterology in Sohag University Hospital during 2015-2016. The Results of the study states that AIMS65 score which was used for the study is found to bethe best simple and applicable scoring system to independently predict mortality in those patients [1].…”
Section: Editor Notementioning
confidence: 99%